Biocompatible and antibacterial silver tantalum oxide thin film by magnetron sputtering for surgical applications / Rodianah Alias - Rodianah , Alias (2019)
Stainless steel (SS) is used extensively for healthcare, hygiene and surgical applications due to its excellent corrosion resistance and adequate mechanical strength. SS grade 316L is the most widely employed stainless steel owing to the high corrosion resistance, good mechanical properties, resistance to sensitization and ease of fabrication. Nonetheless, stainless steel lacks antibacterial activity. To incorporate the antimicrobial characteristic in SS 316L-based surgical instruments, a new nanocomposite thin film coating comprising silver (Ag) and tantalum oxide (Ta2O5) was deposited by physical vapor deposition (PVD) reactive magnetron sputtering in this research. The delamination of the ceramic layers on the SS 316L substrate is one of the major limitations arising from insufficient crystallization and poor adhesion strength. It was found that the adhesion strength improved in a precisely controlled thermal treatment process. The microstructure, morphology, phases, elemental, structure, micromechanical properties, surface chemistry, hydrophobicity, toxicity and antibacterial performance of the as-deposited and annealed thin film specimens were analyzed to determine the characteristics of the developed layers. The thermal treatment setup involved temperatures of 250 to 850 °C that progressively increased the crystallinity and segregation of Ag at the surface. The highest adhesion strength was achieved when the coated samples were annealed at 400 °C, with 154 % improvement achieved compared to the as-deposited layer. The samples annealed at 400 °C demonstrated excellent antibacterial performance against gram-negative Escherichia coli (ATCC 15597) and gram-positive Staphylococcus aureus (NCTC 6571) according to inhibition zone measurements. Ag/Ag-Ta2O5 prepared at 400 °C exhibited significantly superior biocompatibility (cell attachment and proliferation of seeded human bone marrow-derived mesenchymal stromal cells) compared to Ag/Ag-Ta2O5 annealed at 700 °C as well as SS 316L.